PERFORMANCE OF THE NATIONAL NARCOTICS AGENCY OF GRESIK REGENCY IN EFFORT TO PREVENT NARCOTICS ABUSE AMONG YOUTH (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to describe the performance of the National Narcotics Agency of Gresik Regency in an effort to prevent drug abuse among adolescents and to analyze the supporting and inhibiting factors of the National Narcotics Agency of Gresik Regency in efforts to prevent drugs abuse among adolescents. This type of research is descriptive qualitative using data collection methods in the form of interviews, observations, and documentation. The data analysis technique used is an interactive model from Miles and Huberman. The results of this study indicate that the performance of the National Narcotics Agency of Gresik Regency in implementing the narcotics abuse prevention program among adolescents is good. From the indicators of responsiveness, the programs carried out are appropriate to answer the public's needs. From the indicators of responsibility, the programs carried out are in accordance with the existing policies. Meanwhile, from the accountability indicators, the programs carried out are accountable with the decreasing number of adolescent users. The supporting factor for this program is the policy issued by the Central Government and the Gresik Regency Government, while the inhibiting factor is the COVID-19 pandemic.